2009
DOI: 10.1021/jf902861m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiviral Bioactivities of 2-Cyano-3-substituted-amino(phenyl) Methylphosphonylacrylates (Acrylamides) Containing Alkoxyethyl Moieties

Abstract: An efficient reaction under microwave irradiation has been developed for the synthesis of a series of novel 2-cyano-3-substituted-amino(phenyl) methylphosphonylacrylates (acrylamides) II. The products obtained in shorter reaction time with moderate yields are fully characterized by elemental analysis, IR, (1)H, (13)C, and (31)P NMR spectral data. The role of introducing various substituents and the effect of incorporating alpha-aminophosphonates with an alkoxyethyl moiety into the parent cyanoacrylate (acrylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…TMV is known to infect more than 400 plant species such as tobacco, tomato, potato and cucumber to cause tremendous economic loss worldwide 45,46 . Built on our previous studies in this area to treat plant virus diseases 47,48 , our preliminary studies here found that the isatin-derived alkene compound 5k showed a promising 42.6% inhibition rate against TMV infection. The positive control experiment using the commercially used drug Ningnanmycin 45,49 showed 56.2% inhibition rate (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…TMV is known to infect more than 400 plant species such as tobacco, tomato, potato and cucumber to cause tremendous economic loss worldwide 45,46 . Built on our previous studies in this area to treat plant virus diseases 47,48 , our preliminary studies here found that the isatin-derived alkene compound 5k showed a promising 42.6% inhibition rate against TMV infection. The positive control experiment using the commercially used drug Ningnanmycin 45,49 showed 56.2% inhibition rate (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…In recent decades, many efforts have been made to develop novel, potent and structurally concise antiviral agents. A series of chemicals have been found to possess antiviral activity, such as pyrazole derivatives, cyanoacrylate derivatives, α ‐aminophosphonate derivatives, N ‐(pyrimidin‐5‐yl)‐ N ′‐phenylureas and some natural products . However, there are only a few reports on economically viable antiviral chemicals available for application in agriculture, so there is still great scope for further research in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the unsatisfactory cure rate (30-60%) of common antiviral agents (Ningnanmycin, Ribavirin, Virus A, et al) and economic loss of tobacco, many efforts have been done to develop novel, potent and structure concise antiviral agents. Some chemicals, such as triazolyl compounds [3], pyrazole derivatives [4,5], cyanoacrylate derivatives [5,6], a-aminophosphonate derivatives [5,7], N-(pyrimidin-5-yl)-N9-phenylureas [8], and some natural products [9][10][11], have been found to possess antiviral activity. However, there are only a few reports on economically viable antiviral chemicals available for application in agriculture [12], so there still lies a great deal of scope for further research in this field.…”
Section: Introductionmentioning
confidence: 99%